2004
DOI: 10.1007/s11104-005-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of local elevation on soil properties and tree health in remnant eucalypt woodlands affected by secondary salinity

Abstract: More than 2 M ha of remnant vegetation in Australia is predicted to be at risk from shallow water tables by 2050. Currently, vegetation is considered to be at risk where the water table is predicted to be less than 2 m below the soil surface, yet casual observation of areas affected by secondary salinity in the Western Australian wheatbelt has suggested that small differences in elevation (< 0.5 m) are important in determining plant health. In this study, we investigated how small changes in elevation (and hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although within-treatment topography is minimal (typically 610-50 mm), designs of such systems need to take surface elevation into account. Utilization of microtopographic variation in agriculture and agroforestry site design is used to aid the management and application of resources to enable maximum output to be achieved (Cramer et al 2004). The high proportion of variation explained by the environmental variables for the SWL norm data sets highlights the importance of minor topographic variations on a small scale (between piezometers).…”
Section: Implications Of Environmental Trial Variablesmentioning
confidence: 99%
“…Although within-treatment topography is minimal (typically 610-50 mm), designs of such systems need to take surface elevation into account. Utilization of microtopographic variation in agriculture and agroforestry site design is used to aid the management and application of resources to enable maximum output to be achieved (Cramer et al 2004). The high proportion of variation explained by the environmental variables for the SWL norm data sets highlights the importance of minor topographic variations on a small scale (between piezometers).…”
Section: Implications Of Environmental Trial Variablesmentioning
confidence: 99%
“…Here, we investigated the impacts of habitat fragmentation and soil properties on Eucalyptus wandoo Blakely (Myrtaceae), a dominant tree species found across the landscape that has undergone significant recent habitat fragmentation and associated landscape changes through much of its range. Wandoo woodlands tend to occur low in the landscape on valley slopes and floors and therefore may be exposed to the effects of secondary salinity, which in some areas has led to mortality of wandoo trees (Cramer et al, 2004). Salinity-related mortality of wandoo appears to occur as a local ecosystem collapse in response to the breaching of critical salinity thresholds, often following extreme events, rather than as the result of a gradual decline in tree health with increasing salinity (Cramer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Wandoo woodlands tend to occur low in the landscape on valley slopes and floors and therefore may be exposed to the effects of secondary salinity, which in some areas has led to mortality of wandoo trees (Cramer et al, 2004). Salinity-related mortality of wandoo appears to occur as a local ecosystem collapse in response to the breaching of critical salinity thresholds, often following extreme events, rather than as the result of a gradual decline in tree health with increasing salinity (Cramer et al, 2004). Two studies found no relationship between secondary soil salinity and the crown health of live E. wandoo trees (Cramer et al, 2004;Brouwers et al, 2013), but they did not investigate other soil properties or aspects of population ecology such as reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…More than 93% of native vegetation in the wheatbelt has been cleared (Cramer et al 2004), so the fringing vegetation of playa lakes are important remnants of a biologically diverse region that are now threatened by altered hydrological regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Subtle differences of less than 0.2 m in topography can buffer the seasonal effects of salinity and waterlogging, but vegetation can be severely impacted by extreme and episodic events (Cramer et al 2004). There has been a significant decline in annual rainfall in south-west Western Australia and more intense summer rainfall events from 1911 to 1990 (Yu and Neil 1993).…”
Section: Introductionmentioning
confidence: 99%